Polymer extrusion black-box reveal - Wong, Anthony Chi-Ying (Hanser, 2024)
Plastics extrusion is one of the most important industrial processes worldwide. Over past decades, understanding of extrusion technologies has advanced by the global research efforts, but, due to the fact that the metal barrel hinders direct visualizations to be made by the naked eye, the "true" dynamic processing characteristics of extrusion processes remain unclear. Analytical attempts have thus been carried out either by indirect, static empirical approaches or theoretical mathematical analyses. None of them offer a realistic depiction of what takes place inside the barrel during an extrusion process. As such, the barrel can be considered as a "black-box". This book reveals the "true" dynamic extrusion processing characteristics, accumulated from years of research experience based on the novel visualization technique developed by Professor Zhu of the Beijing University of Chemical Technology. The qualitative discussions within provide not only insight into the scientific aspects of the subject, but also information of practical significance for those in the industry who need to perform process and hardware designs and optimizations. Included are conventional mathematical representations of the single- and twin-screw extrusion technologies. This provides a comprehensive foundation for undergraduate courses in, e.g., plastics processing engineering. Other topics covered are specifically selected to provide a comprehensive technical and market-trend background to readers at all levels. The current status and future potential of sustainable and biodegradable polymers are also emphasized